SOCIAL MEDIA AS A FLATFORM IN PUBLIC SPEAKING COURSES - Fendry Gabriel; Mulia Rahman Kandau; Dinar Azizah Arifin; Ayu Melati Ningsih (PHILOLOGY Journal of English Language and Literature, 2022)
Social media is one of the platforms for the public speaking lecture process for students during the pandemic. Various platforms are used to support lecture activities. The purpose of this study is to find out which social media is often used in the public speaking lecture process during the pandemic. The method used is a qualitative method which is intended to explain or describe the phenomenon of which platforms are widely used during the pandemic. Analyzing several journals related to social media which are more effectively used as a platform for the public speaking lecture process. So that, according to several sources, Instagram is a platform that is widely used in lectures in public speaking courses as a platform that supports public speaking activities.